2018
DOI: 10.1002/eqe.3145
|View full text |Cite
|
Sign up to set email alerts
|

On the number of records for structural risk estimation in PBEE

Abstract: Summary Response‐history nonlinear dynamic analysis is an analytical tool that often sees use in risk‐oriented earthquake engineering applications. In the context of performance‐based earthquake engineering, dynamic analysis serves to obtain a probabilistic description of seismic structural vulnerability. This typically involves subjecting a nonlinear numerical computer model to a set of ground‐motions that represent a sample of possible realizations of base acceleration at the site of interest. The analysis r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(23 citation statements)
references
References 34 publications
(56 reference statements)
1
21
0
Order By: Relevance
“…Generally, the nonlinear dynamic analysis is considered the most effective way to proceed, because it allows accurately simulation of the response of the buildings under seismic motion. On the other hand, despite the availability of a huge variety of scientific works about this topic, in practice-oriented applications nonlinear dynamic analysis has difficulty finding space for several reasons: the design code provisions about the assessment of existing buildings are still lacking; there is an objective difficulty in the selection of ground-motions (number of accelerograms, efficiency, sufficiency [5]); a detailed characterization of the cyclic behaviour of structural elements is needed, high time-analysis and computational efforts are required.…”
Section: Introductionmentioning
confidence: 99%
“…Generally, the nonlinear dynamic analysis is considered the most effective way to proceed, because it allows accurately simulation of the response of the buildings under seismic motion. On the other hand, despite the availability of a huge variety of scientific works about this topic, in practice-oriented applications nonlinear dynamic analysis has difficulty finding space for several reasons: the design code provisions about the assessment of existing buildings are still lacking; there is an objective difficulty in the selection of ground-motions (number of accelerograms, efficiency, sufficiency [5]); a detailed characterization of the cyclic behaviour of structural elements is needed, high time-analysis and computational efforts are required.…”
Section: Introductionmentioning
confidence: 99%
“…Past research has shown that such IMs are more efficient in predicting inelastic displacement response than single‐spectral‐ordinate IMs, by virtue of accounting for spectral shape beyond the structure's fundamental period 26 . This efficiency is quantified in terms of the dispersion of structural responses given various levels of the conditioning IM and has the practical result of limiting the amount of dynamic analyses required to obtain risk estimates within a target standard error 27,28 . In fact, this period interval contains almost all Tof the generated ESDoF oscillators, bar a few with Cy<0.12, and therefore Saavg could be a common IM to express the fragilities of all structures considered 29 .…”
Section: Methodsmentioning
confidence: 99%
“…at least 7 signals per 8 intensity levels according to ATC-58-1 (FEMA, 2018)) needs in case of fragility curves' derivation, where special attention has to be paid to response dispersion (Kiani et al 2018). Besides, Baltzopoulos et al (2019) point out that the appropriate number of ground motions is remarkably dependent on the site-specific hazard and influences the achievable level of accuracy.…”
Section: Seismic Input Selection For Nldasmentioning
confidence: 99%